Comparison of femur stiffness measured from DXA and QCT for assessment of hip fracture risk - Luo, Yunhua; Yang, Huijuan (Journal of bone and mineral metabolism, 2019)
Femur stiffness, for example axial and bending stiffness, integrates both geometric and material information of the bone, and thus can be an effective indicator of bone strength and hip fracture risk. Femur stiffness is ideally measured from quantitative computed tomography (QCT), but QCT is not recommended for routine clinical use due to the public concern about exposure to high-dosage radiation. Dual energy X-ray absorptiometry (DXA) is currently the primary imaging modality in clinic. However, DXA is two-dimensional and it is not clear whether DXA-estimated stiffness has adequate accuracy to replace its QCT counterpart for clinical application. This study investigated the accuracy of femur stiffness (axial and bending) estimated from CTXA (computed tomography X-ray absorptiometry) and DXA against those directly measured from QCT. Proximal-femur QCT and DXA from 67 subjects were acquired. For each femur, the QCT dataset was projected into CTXA using CTXA-Hip (Mindways Software, Inc., USA). Femur stiffness at the femoral neck and intertrochanter were then calculated from QCT, CTXA and DXA, respectively, and different elasticity-density relationships were considered in the calculation. Pearson correlations between QCT and CTXA/DXA measured stiffness were studied. The results showed that there were strong correlations between QCT and CTXA derived stiffness, although the correlations were affected by the adopted elasticity-density relationship. Correlations between QCT and DXA derived stiffness were much less strong, mainly caused by the inconsistence of femur orientation in QCT projection and in DXA positioning. Our preliminary clinical study showed that femur stiffness had slightly better performance than femur geometry in discrimination of hip fracture cases from controls.